Late Pancreatic Fistula After Pancreaticoduodenectomy: A Case Report and Review of the Literature - Perez, Numa P. (Case Rep Pancreat Cancer, 2016)
Background: More than 100 years after its conception, the pancreaticoduodenectomy (PD) remains a challenging procedure with significant morbidity, often due to a postoperative pancreatic fistula (POPF). Factors related to patient physiology, tumor anatomy/pathology, and surgeon/surgical technique have been studied, yielding results at times conflicting and difficult to reproduce. We present a case of a late POPF along with a brief review of the current literature. Case Presentation: The patient is a 55-year-old female with a 20 pack-year smoking history and no history of alcohol abuse, who presented for evaluation of new nausea. Her laboratory tests and computed tomography (CT) imaging were suggestive of biliary obstruction. She was found to have an invasive ampullary adenocarcinoma and subsequently underwent a classic PD. She developed a POPF, managed through a closed suction drain placed intraoperatively. Her course was complicated by the development of an intra-abdominal abscess, managed percutaneously through CT-guided placement of two drains, subsequently removed without issues. She recovered uneventfully until 8 months after the operation, when she presented with abdominal pain and pancreatitis. She was found to have an intra-abdominal collection, again managed percutaneously via CT-guided drainage. This time, the amylase and lipase levels of the drainage fluid were 21,860 and 86,650 U/L, respectively, and cultures were sterile. Upon workup of her pancreatic fistula, a severe stricture at the pancreaticojejunostomy (PJ) was identified. She underwent endoscopic placement of a Hobbs stent by the GI service. Conclusion: Although commonly diagnosed in the days to weeks after a PD, we present a case of a POPF that manifested 8 months after the initial operation in association with a PJ stricture. This case highlights the importance of considering the diagnosis even months after the operation in a patient who presents with symptoms of pancreatitis and/or imaging findings consistent with an intra-abdominal collection.